Stigma Stories Rhetoric, Lived Experience, and Chronic Illness (The Ohio State University Press, 2022)
In Stigma Stories: Rhetoric, Lived Experience, and Chronic Illness, Molly Margaret Kessler focuses on ostomies and gastrointestinal conditions to show how stigma is nearly as central to living with chronic conditions as the conditions themselves. Drawing on a multi-year study that includes participant observations, interviews, and rhetorical engagement with public health campaigns, blogs, social media posts, and news articles, Stigma Stories advocates for a rhetorical praxiographic approach that is attuned to the rhetorical processes, experiences, and practices in which stigma is enacted or countered. Engaging interdisciplinary conversations from the rhetoric of health and medicine, disability studies, narrative medicine, and sociology, Kessler takes an innovative look at how stigma functions on individual, interpersonal, and societal levels. In doing so, Kessler reveals how stories and lived experiences have much to teach us not only about how stigma functions but also about how it can be dismantled.